1996
DOI: 10.1021/ma950622i
|View full text |Cite
|
Sign up to set email alerts
|

Information on the Monomer Sequence of Poly(lactic acid) and Random Copolymers of Lactic Acid and Glycolic Acid by Examination of Static Secondary Ion Mass Spectrometry Ion Intensities

Abstract: Static secondary ion mass spectrometry (SSIMS) has been used to analyze a range of poly-(lactic acid)s (PLA) and copolymers of lactic and glycolic acids (PLGA). Ion assignments for the full range of radical cations observed are presented, along with the observation of chain end contribution to the SSIMS spectra in the case of low molecular weight PLA. The ion intensities within different radical cation series in PLGA have been compared with theoretical intensity distributions. In the case of random copolymers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 20 publications
6
42
0
Order By: Relevance
“…Our data, however, lie somewhere between the purely monomeric and purely dimeric model, and this was taken as evidence that trans-esterification occurs during synthesis. [11,13] We now extend the previous model to show that it is possible, using SIMS, to determine the degree of trans-esterification. Assuming that the probability of encountering an ester link that has undergone a trans-esterification reaction is independent of the nature of the adjacent repeat units, we can assign a global probability, P T , which represents the ratio of trans-esterified bonds to the total number of ester bonds.…”
Section: Gllmentioning
confidence: 79%
See 2 more Smart Citations
“…Our data, however, lie somewhere between the purely monomeric and purely dimeric model, and this was taken as evidence that trans-esterification occurs during synthesis. [11,13] We now extend the previous model to show that it is possible, using SIMS, to determine the degree of trans-esterification. Assuming that the probability of encountering an ester link that has undergone a trans-esterification reaction is independent of the nature of the adjacent repeat units, we can assign a global probability, P T , which represents the ratio of trans-esterified bonds to the total number of ester bonds.…”
Section: Gllmentioning
confidence: 79%
“…Positive ion spectra are employed in this study, since SSIMS positive ion spectra are found to be informative with regards to PLGA [13,32] and the ToF-SIMS spectrum of PLGA is given in Ref. [13].…”
Section: Ssims and G-sims Analysis Of Plgamentioning
confidence: 99%
See 1 more Smart Citation
“…The SSIMS spectrum was in close agreement with the spectra obtained from the previous studies. [14,15] However stability of the structures given above for m/z 100 and 101 are extremely strained, and therefore, unlikely that the ions possess these structures. This was discussed in the previous paper by Shard et al, where it was proposed that if the cyclic structures are allowed to exist they would exist as intermediate structures, and there should be a 'scrambling' of the isotopically different oxygen atoms, which would be evident in further fragmentation of the ion.…”
Section: Plamentioning
confidence: 99%
“…This was discussed in the previous paper by Shard et al, where it was proposed that if the cyclic structures are allowed to exist they would exist as intermediate structures, and there should be a 'scrambling' of the isotopically different oxygen atoms, which would be evident in further fragmentation of the ion. [15] At m/z 101, there was also another peak present, which was assigned as C 4 H 5 O 3 + with a deviation of 3.8 ppm. For PLA, significant broadening of the mass peaks was observed for m/z > 300.…”
Section: Plamentioning
confidence: 99%